2014
DOI: 10.3233/bmr-130426
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of forward head posture in females: Observational and photogrammetry methods

Abstract: Our results showed that, craniovertebral angle method may discriminate the females with moderate-severe and non FHP more accurate than head position angle and head tilt angle. The photogrammetric method had excellent inter and intra rater reliability to assess the head and cervical posture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
156
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 43 publications
7
156
1
8
Order By: Relevance
“…It was reported in a previous study that normal CCA was 53.2°-56.8° which was measured using Adobe Acrobat software [7]. In our current study, the mean CCA was 47.43 o ±7.97 o , which is less than normal ranges (53.2°-56.8°)(ref).…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…It was reported in a previous study that normal CCA was 53.2°-56.8° which was measured using Adobe Acrobat software [7]. In our current study, the mean CCA was 47.43 o ±7.97 o , which is less than normal ranges (53.2°-56.8°)(ref).…”
Section: Discussioncontrasting
confidence: 38%
“…In our current study, the mean CCA was 47.43 o ±7.97 o , which is less than normal ranges (53.2°-56.8°)(ref). In the study by Salahzadeh et al, it was found that based on digital photogrammetry, 50% of their study participants had a slight FHP, and this was classified as "normal FHP" with subjective classification [7]. This indicates that even people without a history of neck pain demonstrate a slight FHP.…”
Section: Discussionmentioning
confidence: 98%
“…Participants were assigned to the groups according to the measurement of the craniovertebral angle. Individuals with a craniovertebral angle that was less than 49 ° were allocated to the forward–head posture group; those with a craniovertebral angle of greater than 50 ° were placed in the control group . All participants were right‐handed to eliminate any possible effects of handedness on muscle thickness .…”
Section: Methodsmentioning
confidence: 99%
“…An evaluation of the head posture was conducted by measuring the craniovertebral angle, which is the angle between the horizontal line passing through the seventh cervical spinous process (C7) and the line extending from the tragus of the ear to the spinous process of C7. Digitalized lateral‐view photography was used to measure the craniovertebral angle.…”
Section: Methodsmentioning
confidence: 99%
“…Those who were not doing regular or systematic exercise at the time of subject selection and those who showed forward head posture over 2.5cm in the overall body posture measurement system were chosen as the subjects (Salahzadeh et al, 2014). All the subjects were provided with a sufficient explanation about the study content and participated in the study after signing a consent form.…”
Section: Study Subjectsmentioning
confidence: 99%